Measuring the willpower of university students (Journal of the College of Basic Education, 2022)
The current research aims to identify the willpower of university students, and for the purpose of achieving the goal of the research, the researchers used the descriptive approach, and the researchers prepared a measure of willpower, and for the purpose of conducting a statistical analysis of the measure of willpower, a sample consisting of (400) university students was selected, and the sample was chosen randomly from Students of the colleges of Al-Mustansiriya University, and the researchers extracted the psychometric characteristics of the scale and the use of statistical indicators.